Using Ground Penetrating Radar Methods to Investigate Reinforced Concrete Structures - Tosti, Fabio; Ferrante, Chiara (Surveys in geophysics, 2020)
This paper provides an overview of the existing literature on the subject of ground penetrating radar (GPR) methods for the investigation of reinforced concrete structures. An overview of the use of concrete and reinforced concrete in civil engineering infrastructures is given. A review of the main destructive and non-destructive testing methods in the field is presented, and an increase in the use of GPR to reinforced concrete structures is highlighted. It was also observed that research in some application areas has been predominantly or exclusively carried out at a laboratory scale, and that similarly, other more application-oriented research has been developed only on real-life structures. The effectiveness of GPR in these areas is demonstrated. Furthermore, a case study is presented on a new methodological and data processing approach for the assessment of reinforced concrete structures using a high-frequency dual-polarised antenna system. Results have proven the advantages of using the proposed methodology and GPR system in order to improve the detectability of rebars, including secondary bottom lines of reinforcement. The horizontal polarisation was proven to be more stable compared to the vertical. Finally, it has been demonstrated that a more accurate location of the rebars in a high-density grid mesh arrangement can be obtained by means of data migration processing with a scan spacing of 5 cm and wave velocity information through the use of the hyperbola fitting method from at least 30% of the targets.